2015
DOI: 10.4238/2015.june.11.1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the PPARγ gene and their association with metabolic syndrome in Uyghurs and Kazakhs from Xinjiang, China

Abstract: ABSTRACT. We investigated the association between polymorphisms rs1801282 and rs3856806 of the PPARγ gene and metabolic syndrome (MS) among Uyghurs and Kazakhs. Mass spectrometry techniques were used to detect the PPARγ genotypes rs1801282 and rs3856806 in 987 subjects, CC genotype and C allele frequencies were 83.6 and 91.7%, respectively, at rs1801282 in Kazakhs, which were higher than those in Uyghurs (72.3 and 85.0%, respectively; P < 0.05). CC genotype and C allele frequencies were 73.6 and 85.3%, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The research carried out by Chen et al among Uyghurs demonstrated that the presence of the C/C genotype of the PPAR-γ rs1801282 polymorphism was a stronger contributor to higher systolic blood pressure than the C/G and G/G genotypes [ 53 ]. Similar conclusions were also drawn by other authors interested in the influence of this polymorphism on the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…The research carried out by Chen et al among Uyghurs demonstrated that the presence of the C/C genotype of the PPAR-γ rs1801282 polymorphism was a stronger contributor to higher systolic blood pressure than the C/G and G/G genotypes [ 53 ]. Similar conclusions were also drawn by other authors interested in the influence of this polymorphism on the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…It was most likely that among Ppar isoforms, PPAR γ was the major regulator of UCP2 in high-fat diet [ 14 ]. One study based on Chinese Han population showed that functional SNPs of PPAR γ were associated with MetS [ 15 ]. The relationship between potential functional SNPs and diabetes remains unknown.…”
Section: Introductionmentioning
confidence: 99%